How have Enterococcal bacteremias progressed in the last 5 years? Epidemiology, resistance to antimicrobials, risk factors, complications - Nuran Sarı; Nurefşan Tuba Kurt; Özlem Kurt Azap (Journal of Global Antimicrobial Resistance)
AIM: It was aimed to investigate the epidemiological and antimicrobial resistance changes in enterococcal bacteremia over the years and the risk factors for mortality. It is intended to be a guide in patient follow-up and treatment. Backgraund: Enterococci are found in the intestine and can cause bacteremia, endocarditis, and urinary tract infections. Bacteremias can have a complicated course and be fatal. METHODS: Between January 2020 and June 2024, Enterococcus species grown in blood cultures, interventions, comorbidities, resistance status, risk factors, and mortality were investigated retrospectively. RESULTS: Enterococcal bacteremia was detected in 237 patients. 220 (50.6%) of the patients were women. The average age of the patients was 69.2±15.87 (minimum 21, maximum 99). Enterococcus faecium was the most frequently detected agent (56.1%) (Figure 1). Antimicrobial resistance, presence of pneumonia, sepsis, mechanical ventilation, and concomitant COVID-19 were found to be significantly higher in mortal patients (p<0.05). Endocarditis was present in 11 patients, abscess was present in 20 patients, and spondylodiscitis was present in 3 patients. Enterococus faecium was not found to be higher in men, in the presence of immunosuppression, hospitalization in the last 3 months, and presence of an intrabdominal focus. Additionally, resistance to vancomycin (22%) ampicillin (%91) gentamicin (%62), imipenem (80%) and teicoplanin (19%) is significantly higher (p<0.05) (Table 1). 182 (76.8%) patients died. CONCLUSION: It should not be forgotten that enterococcal bacteremias have a high mortality rate and may have a complicated course. It should be kept in mind that antibiotic resistance is high in E. faceium.